TRAINING FOR UNCERTAINTY - Statev, Vladimir (Horizons - International Scientific Journal, 2021)
The complexity of today’s environment places humanity under the pressure of coping with the ever-increasing levels of uncertainty. The paper attempts to highlight the need of training the individual for facing this problem. The focus is set on the decision-making process as a function of the human mind. It also touches on some of the popular strategies and tactics for dealing with uncertainty and making wellfounded choices.